Living Through the Chaos: Rethinking Ecological Dimensions of Suicide with Young Women and Femmes Facing Housing Injustice - Santos Dunn, Nicole; Ansloos, Jeffrey (Atlantis)

(untitled) (Mount Saint Vincent University, 2025)
Suicidality among young women and femmes facing housing injustice is an urgent yet under-explored public health issue in Canada. This study highlights the invisibility of “hidden homelessness” and moves beyond individual risk factors to examine how structural, relational, and political forces shape distress. Using narrative inquiry and life history methods, the research identifies four key themes: 1. When a Non-No is a Yes, 2. Unsavoury People and Other Ruptures, 3. Inconsistency and Bouncing Around, and 4. Organized Abandonment and Chaos, Chaos, Chaos, Chaos. These themes elucidate the intersections of gendered violence, systemic neglect, and organized abandonment in shaping suicide risk and survival strategies. The study advocates for justice-oriented, non-coercive approaches to suicide prevention, and emphasizes relational trust and policies that address housing injustice. Strengths, limitations, and future research directions are also discussed.